Transforming lives: the power of an Australian enabling education. Issue 7 (10th November 2022) - Syme, Suzi; Roche, Thomas; Goode, Elizabeth; Crandon, Erin
ABSTRACT: This study examines the impact of an Australian enabling program, underpinned by critical pedagogy, on students' academic and professional success. Qualitative focus group data were collected from individuals who had completed an enabling program at a regional Australian university and progressed to undergraduate study. Quantitative data comparing the academic achievement of enabling and non-enabling students across a six-year period were also analysed. Together, the data present a compelling picture of the transformative power of enabling education underpinned by critical pedagogy. Students who completed the enabling program had higher success rates, grade point averages (GPAs) and retention rates than their non-enabling peers. They were also empowered to overcome limiting beliefs about their academic and professional potential, which in turn led to success in their studies and careers that they had not previously imagined possible.